The experiences of female educators with regard to promotion posts in educational institutions - Masoga, Morotola Rebeccah (My University, 2011)
The purpose of the study was to investigate the experiences of female educators with regard to promotion posts in educational institutions such as schools. The problem which led to the investigation was that female educators allege that they are discriminated against with regard to promotion posts. Hence teaching is predominantly occupied by women but they are under-represented in the management positions. The study was ethnographic and qualitative because the researcher tried to understand the complex settings through the eyes of the informants and assume that, to understand a social setting, one needs to connect the observed behaviour with the rationales for that behaviour. Human life was studied as it was related to education. The literature review highlighted why women do not occupy high positions in management. The study also focused on the perception held by most stakeholders with regard to promotion posts. The study indicated what causes female educators not to occupy higher management posts and strategies that can be employed in addition to the experience of female educators with regard to promotion posts in educational institutions. Data was collected through interviews in order to provide in depth understanding of what is studied. Sample selected was purposeful and non random. Data was analyzed inductively by organizing data into categories and identifying relationships among the categories. Data was selected, categorized, compared, synthesized and interpreted. Data was also analyzed by using descriptive statistical tables. The study discovered some aspects that support what female educators experienced in schools such as discrimination, harassment, negative attitudes, unfair-treatment, inferiority complex and gender-bias which lead to small number of female educators to be in the managerial positions and further research was recommended.
Thesis (M.Ed. (Educational Management)) -- University of Limpopo, 2011
Keywords: Female educators; Promotion posts; Educational institutions; Discrimination